2t-28=-40+4t

Simple and best practice solution for 2t-28=-40+4t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t-28=-40+4t equation:


Simplifying
2t + -28 = -40 + 4t

Reorder the terms:
-28 + 2t = -40 + 4t

Solving
-28 + 2t = -40 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-28 + 2t + -4t = -40 + 4t + -4t

Combine like terms: 2t + -4t = -2t
-28 + -2t = -40 + 4t + -4t

Combine like terms: 4t + -4t = 0
-28 + -2t = -40 + 0
-28 + -2t = -40

Add '28' to each side of the equation.
-28 + 28 + -2t = -40 + 28

Combine like terms: -28 + 28 = 0
0 + -2t = -40 + 28
-2t = -40 + 28

Combine like terms: -40 + 28 = -12
-2t = -12

Divide each side by '-2'.
t = 6

Simplifying
t = 6

See similar equations:

| -9-5y=34 | | 125/10+x=18.10 | | 31/2+13/4 | | X^2+2x^2=25 | | -16x*x+200x+4=0 | | -(4A-3B)= | | x-0.6=8.75 | | 344+36d=500 | | 9-7y=4(1-3x) | | 33s=-231 | | (n+2)*4=28 | | 4x-3/4-2x+5/4=10 | | 15x+10=6x+28 | | (-2y-6x)(-5)= | | 4x-7/8+x=4x+7/4+3 | | 300-20=20 | | 6-9x=54-23x | | 9y+1=8y-5 | | 6x+2=4/x+1 | | 7-3x=-4x | | 5x+12=4/8 | | 1/5(2X-6)=3 | | -88+7x=-85-9x | | y=36-3x^2-2x^3 | | -4/5x+2/25x+1/15x | | 4(6c-6)= | | p^2-p-1=0 | | 9/2=8*1/8 | | 137-2x=5x+11 | | 10x^2+17x-42=0 | | 4(tan)x=1 | | a(a-17)=(-60) |

Equations solver categories